ANALISIS PENGADAAN BAHAN BAKU DAN PENDAPATAN AGROINDUSTRI IKAN ASIN TERI DI KECAMATAN KALIANDA, KABUPATEN LAMPUNG SELATAN - Euis Kartika; Fembriarti Erry Prasmatiwi; Eka Kasymir (Lampung University, 2022)
The purposes of this research are to analyze the processing and determine the process of raw materials procurement that corresponds to six right (on time, right place, right quality, right quantity, the right type, and the right price), and to analyze income of anchovy fish agroindustry in Kalianda District, South Lampung Regency. This location is selected purposively for it is the center of salted anchovy producers in Kalianda. This study is included census survey method in the villages of Maja and Merak Belantung. The data were collected in December 2019 - January 2020 and analyzed by using descriptive analysis of quantitative and qualitative. The results of this study indicated that the six components of raw material procurement was right during the east wind and normal monsoon, but was not on time and not in the right quantity during the west wind season. On the west monsoon revenue over cash and total cost is IDR3,637,031 and IDR122,114 with R/C values of 1.20 and 0.99. The income on cash and on total costs respectively during the east wind season is IDR241,702,427 and IDR209,674,762 with R/C of 1.29 and 1.25, the normal wind season of IDR56,225,240 and IDR50,536,536 with R/C of 1.20 and 1.18.Key words: agroindustry,income, moonson, salted anchovy